NILAI EDUKASI MITOS DAN RELEVANSINYA DENGAN PENANAMAN NILAI PADA KELUARGA MINANGKABAU KONTEMPORER: TINJAUAN AWAL - Yunarti .; Winda Rahmadani (Universitas Andalas, 2017)
Joseph Campbell explains one of the four mythical functions is a pedagogic function that is how humans live life as human beings under any circumstances. Some forms of folklore with pedagogic educative function are as a tool or complement in education and enculturation values such as stories to educate children disciplined, obedient, diligent and intelligent. The enculturation process to ensure the individual achieves maturity and cultural maturity so as to support the social order. In addition to the family as the first institution for the enculturation values in children, the social environment system that becomes interaction area will also affect each other's attitude and parenting ways and the environment. From the preliminary research, it was concluded that the observed myths of education were no longer present in the daily lives of the five families of informants. On the 5 myths traced, only the Malin Kundang myth is still well known. The substance of the values contained in the myth is accepted but is considered to be no longer to be found in the realities of everyday life. In the changing context, the enculturation process of the Minangkabau has shifted along with the swift entry of new values through new communication media